Experiencing the practice of statistics with simple experiments. Issue Volume 30:Issues 4(2018) (2nd October 2018) - Hamada, Alexandra J.; Hamada, Christina A.; Hamada, Masaru; Hamada, Michael S.
Key Points: This article illustrates the practice of statistics through simple experiments. In running experiments that involve blowing bubbles, collecting rain, and spinning propellers, issues arise that in the practice of statistics require being carefully addressed to correctly apply statistical methods. Addressing these issues involves developing statistical models, simulation, and optimization. Sometimes the solutions require research, that is, applied research.